2015
DOI: 10.1007/s00265-015-2012-z
|View full text |Cite
|
Sign up to set email alerts
|

Among-year variation in the repeatability, within- and between-individual, and phenotypic correlations of behaviors in a natural population

Abstract: When mean behaviors correlate among individuals, they form behavioral syndromes. One way to understand the evolution of such a group-level phenomenon is to compare horizontally patterns of correlations among populations (or species) or follow longitudinally the same population over years in the light of parallel differences in the environment. We applied the longitudinal approach to 8-year field data and analyzed phenotypic correlations, and their within- and between-individual components, among three behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 64 publications
1
31
0
8
Order By: Relevance
“…While these studies examined between-population differences, similar patterns have been observed within populations across time in collared flycatcher birds ( Ficedula albicollis ). Behavioral correlations appeared and disappeared across years that coincided with changes in the density and age composition of the bird population, which could reflect changes in resource availability 65 . Our results suggest that the ecological pressures acting on the WC population shaped different behavioral patterns compared to those resulting from artificial selection.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…While these studies examined between-population differences, similar patterns have been observed within populations across time in collared flycatcher birds ( Ficedula albicollis ). Behavioral correlations appeared and disappeared across years that coincided with changes in the density and age composition of the bird population, which could reflect changes in resource availability 65 . Our results suggest that the ecological pressures acting on the WC population shaped different behavioral patterns compared to those resulting from artificial selection.…”
Section: Discussionmentioning
confidence: 92%
“…The local ecological factors that might have contributed to shaping the WC animals’ behavior are not known. It is possible that some population differences or behavioral correlations may only emerge under certain local environmental conditions 16,46,65 . Several studies that investigated wild zebrafish populations found that predation and water flow can explain population differences in behavioral correlations between boldness, aggression and activity 16,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Garamszegi et al. () studying a wild population of collared flycatchers ( Ficedula albicollis ) demonstrated that strength and direction of behavioural correlations could change among years. In manipulative experiments, Horváth, Martín, López, Garamszegi, and Herczeg () and Horváth, Mészáros, et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Møller ) or low (Garamszegi et al . 2015a) repeatability. Therefore, we cannot exclude that some amount of the within‐population variance originates from within‐individual plasticity, at least in some species.…”
Section: Discussionmentioning
confidence: 99%